Relationship of polymorphism of genes GSTT1 and GSTM1 on treatment efficacy of the genital endometriosis - V. N. Tkachyov; A. S. Yurchenko; I. D. Yevtushenko; I. O. Naslednikova; V. V. Novitsky; O. I. Urazova; K. S. Kublinsky; P. A. Zakharova; N. S. Menshikova (Бюллетень сибирской медицины, 2012)
Clinical and molecular-genetic examination and treatment of 140 patients with genital endometriosis is presented. Integrated treatment included surgery laparoscopic method and application of hormonal preparations (agonists gonadotropin releasing hormones, combined oral contraceptives). The most effective method of drug therapy of endometriosis after prior surgical correction was the appointment of agonists gonadotropin releasing hormone. The effectiveness of drug therapy of endometriosis correlated with special genes polymorphism of enzymes of biotransformation phase is "functionally defective genotypes 0/0" GSTT1 and GSTM1 0/0 are associated with low efficiency of medical treatment of the genital endometriosis. Assignment of drug therapy of endometriosis based on genetic polymorphism of an organism of the patient is appropriate.